Gender Harmony and Family Resilience on Online Motorcycle Drivers in Ponorogo Regency During the Covid-19 - Evi Muafiah; Ulin Nadya Rif ’atur Rohmah; Neng Eri Sofiana; Maslathif Dwi Purnomo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The COVID-19 pandemic has significantly impacted the economic stability of informal workers, including motorbike taxi drivers, affecting not only their financial well-being but also their social and psychological resilience. This study examines the role of gender harmony in reinforcing family resilience among motorbike taxi drivers in the Ponorogo Regency during the crisis. Using a qualitative descriptive approach, data was collected through in-depth interviews and analyzed within the framework of gender harmony theory. The findings reveal that gender harmony played a crucial role in mitigating economic, social, and psychological challenges. Families that adopted a dual-income model, allowing both spouses to contribute financially, exhibited greater economic resilience. Social resilience was fostered through cooperation in domestic and public roles, enhancing marital satisfaction. Psychological resilience was reinforced by effective communication, mutual support, and religious values that provided coping mechanisms during the crisis. However, gender inequality persisted in some families where women faced a double burden of financial and domestic responsibilities. These findings highlight the importance of gender-responsive strategies in strengthening family resilience amid crises. Future research should explore long-term implications of gender harmony on economic and psychological well-being in post-pandemic recovery.